Respuesta :

2ab x cos (C) = 7 because

a^2 + b^2 - 2ab x cos(C) = c^2
2ab x cos(C) = a^2 + b^2 - c^2
2ab x cos(C) = 2^2 + 2^2 - 1^2
2ab x cos (C) = 7

Answer:

(D)[tex]7=2abcosC[/tex]

Step-by-step explanation:

It is given from figure that c=1, a=2 and b=2, thus using the law of cosines, we get

[tex]c^2=a^2+b^2-2abcosC[/tex]

Substituting the given values, we get

[tex](1)^2=(2)^2+(2)^2-2abcosC[/tex]

[tex]1=4+4-2abcosC[/tex]

[tex]1=8-2abcosC[/tex]

[tex]1-8=-2abcosC[/tex]

[tex]-7=-2abcosc[/tex]

[tex]7=2abcosC[/tex]

Thus, the value of [tex]2abcosC[/tex] is [tex]7[/tex].

Hence, option (D) is correct.

ACCESS MORE